Shareholders and Firm Value for Manufacturing Companies Listed in Indonesia Stock Exchange - Muhammad Rifky Santoso; Iskandar Muda (Journal of Economics, Business, and Accountancy Ventura, 2020)
Domestic institutional shareholders and foreign shareholders differently influence firm value. Using panel data from the manufacturing company listed in the Indonesia Stock Exchange (IDX), from 2014 to 2017, and regression analysis, these types of shareholders have a positive and significant impact on the firm value with an inverted U-shaped. The influence of domestic institutional share-holders to the firm value is more significant than that of the foreign shareholder indicated by the coefficient value from the regression results. The best combination of shareholders to obtain the optimum firm value are the domestic institutional shareholder no more than 35.26 percent and the foreign shareholder no more than 47.61 percent. The greater share ownership will increase shareholder intervention and benefit the majority shareholder. Effective monitoring improvements are needed so that the majority of shareholder intervention can be reduced.